2019
DOI: 10.3389/fnhum.2019.00194
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Prefrontal Recruitment During Walking After Stroke: Influence of Individual Differences in Mobility and Cognitive Function

Abstract: Background : Functional near-infrared spectroscopy (fNIRS) is a valuable neuroimaging approach for studying cortical contributions to walking function. Recruitment of prefrontal cortex during walking has been a particular area of focus in the literature. The present study investigated whether task-related change in prefrontal recruitment measured by fNIRS is affected by individual differences in people post-stroke. The primary hypotheses were that poor mobility function would contribute to prefronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 78 publications
3
32
0
Order By: Relevance
“…In sum, only two of the six participants (33%) were able to independently complete all six BLTT sessions. This finding is akin to previous walking rehabilitation studies that have reported that baseline walking severity level may influence training ability ( Burke et al , 2014 ; Dobkin et al , 2014 ; Bernhardt et al , 2016 ; Boyd et al , 2017 ), which may be associated with the magnitude of post-stroke cognitive and physical limitations in this subgroup, ( Kurz et al , 2012 ; Hawkins et al , 2018 ; Chatterjee et al , 2019 ). Therefore, it is possible that our BLTT protocol, in its present form, is too tasking for severely impaired individuals and future protocols will need modification to further accommodate those with severe walking impairment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In sum, only two of the six participants (33%) were able to independently complete all six BLTT sessions. This finding is akin to previous walking rehabilitation studies that have reported that baseline walking severity level may influence training ability ( Burke et al , 2014 ; Dobkin et al , 2014 ; Bernhardt et al , 2016 ; Boyd et al , 2017 ), which may be associated with the magnitude of post-stroke cognitive and physical limitations in this subgroup, ( Kurz et al , 2012 ; Hawkins et al , 2018 ; Chatterjee et al , 2019 ). Therefore, it is possible that our BLTT protocol, in its present form, is too tasking for severely impaired individuals and future protocols will need modification to further accommodate those with severe walking impairment.…”
Section: Discussionsupporting
confidence: 77%
“…For example, stroke commonly impacts chronologically older individuals, which is associated with a decline in gait speed, joint range of motion and spatiotemporal ability ( Stacy et al , 2007 ). Moreover, functional neuroimaging studies have reported an increased tendency for prefrontal compensatory recruitment during normal walking in this population ( Kurz et al , 2012 ; Chatterjee et al , 2019 ). In addition, backward walking is characteristically more physically demanding than walking forward ( Flynn et al , 1994 ; Terblanche et al , 2005 ) and requires movement patterns that tend to be particularly difficult after stroke (i.e.…”
Section: Introductionmentioning
confidence: 89%
“…Other recent findings suggest that people with poorer mobility such as elders or neurological patients exhibits a higher PFC activation than control groups during walking, reflecting a higher cognitive demand (7,9). In stroke, lower mobility was associated with a higher (and saturated) recruitment of the PFC in walking tasks (7,10). Hence, the challenge for upcoming studies investigating brain activation during walking in stroke patients relies on a better understanding of the relationship between the cortical control of gait and functional independence.…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS has also provided evidence of "CRUNCH-like" changes in cortical activity during walking. Evidence of prefrontal over-recruitment during typical steady state walking has been reported in several populations with compromised mobility, including older adults (Chen et al, 2017;Mirelman et al, 2017;Hawkins et al, 2018) and people with stroke (Hawkins et al, 2018;Chatterjee et al, 2019), Parkinson's disease (Maidan et al, 2016a,b), and multiple sclerosis (Hernandez et al, 2016). This is potentially consistent with recruitment of attentional resources to maintain functional walking and compensate for weakness, sensory loss, and/or other impairments affecting control of walking (Clark, 2015).…”
Section: The Crunch Framework Applied To Motor Controlmentioning
confidence: 83%
“…These data are consistent with over-recruitment of prefrontal resources in older adults during typical steady state walking. Another study reported data suggesting a ceiling effect for prefrontal recruitment during complex walking in adults poststroke (Chatterjee et al, 2019). The participants performed dual-task walking (with serial-7 subtraction) while prefrontal activity was recorded with fNIRS.…”
Section: The Crunch Framework Applied To Motor Controlmentioning
confidence: 99%